Measurement Method Options to Investigate Digital Screen Technology Use by Children and Adolescents: A Narrative Review - Amber Beynon; Danica Hendry; Charlotte Lund Rasmussen; Andrew L. Rohl; Rebecca Eynon; George Thomas; Sarah Stearne; Amity Campbell; Courtenay Harris; Juliana Zabatiero; Leon Straker (MDPI AG, 2024)
The role and potential impact of digital screen technology in the lives of children is heavily debated. Current evidence is limited by the weakness of measures typically used to characterise screen use, predominantly proxy- or self-reports with known inaccuracy and bias. However, robust and detailed evidence is needed to provide practical trustworthy guidance to families and professionals working with families. The purpose of this paper is to support researchers to select measurement method(s) that will provide robust and detailed evidence. The paper outlines the challenges in measuring contemporary screen use by children, using a child-technology interaction model to organise considerations. A range of different methods used to measure digital screen technology use in children and adolescents (i.e., questionnaires, diaries, electronically prompted sampling, direct observation, fixed room cameras, wearable/portable cameras, audio recorders, screen-device onboard logging, remote digital trace logging and proximity logging) are described along with examples of their use and constructs typically measured as well as a summary of the advantages and disadvantages of each method. A checklist and worked examples are provided to support researchers determining the best methods or combination of methods for a research project.